Anuṣṭhāna Yōga Vedānta of Yogacharya Raparthi Rama Rao: A comprehensive system of Yōga and Vedānta for the modern age - Suneetha Kandi (Wolters Kluwer Medknow Publications, 2017)
Background: Anuṣṭhāna Yōga Vedānta (AYV) is a comprehensive system developed by Yogacharya Raparthi Rama Rao, who attained the state of jīvaṇmukti (liberated while living). He was the spiritual head of Yoga Consciousness Trust, Vizinigiri, Andhra Pradesh, India. AYV comprises two integrated parts of yōga and vedānta emphasizing on the applied aspects of both. Aim: The aim of the current study was to focus on exploration and analysis of the AYV methodology and techniques. Method: Extensive review of five books written by Yogacharya in English represent the AYV method. One of the books was on biographical details of Yogacharya including his selected works and letters. The researcher attended lectures, listened to compact disc recordings, and interacted personally with Yogacharya for clarification and correction of concept and methodology of AYV. Results: Anuṣṭhāna Yōga is the amalgamation of Karma, Bhakti, Maṇtra, Kuṇḍalini, Jñāna, and Rāja Yōgas. All these yōgas are practiced in a systematic manner, initially with a focus on attaining the biṇdu or chaitaṇya darśan, and then practicing to be in the awareness of the chaitaṇya. Anuṣṭhāna vedānta deals with imparting knowledge that helps in analyzing and realizing the nature of one's true self. Conclusion: Yogacharya developed a systematic methodology of achieving the objectives of yōga and vedānta, which is tailored to the needs and levels of the modern person and is a surest, swiftest, and safest method. The stage-by-stage learning process of AYV guides all types of sādhakas in a phased manner and helps them progress to reach the goal.